2015
DOI: 10.1634/theoncologist.2014-0266
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Plasma and Urinary 2-Hydroxyglutarate to Identify Patients With Isocitrate Dehydrogenase-Mutated Glioma

Abstract: Background. Mutant isocitrate dehydrogenase (IDH) 1/2 enzymes can convert a-ketoglutarate into 2-hydroxyglutarate (2HG). The aim of the present study was to explore whether 2HG in plasma and urine could predict the presence of IDH1/2 mutations in patients with glioma. Materials and Methods. All patients had histological confirmation of glioma and a recent brain magnetic resonance imaging scan showing the neoplastic lesion. Plasma and urine samples were taken from all patients, and the 2HG concentrations were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 27 publications
3
39
2
1
Order By: Relevance
“…Although it would appear intuitive that urine 2-HG levels would be comparatively elevated, as we have found, among a population of patients with IDH-mutant disease, the reason for the discordance with a previous report that observed lower urinary 2-HG levels in patients with IDH1-mutant compared with IDH-WT gliomas is unclear [28]. However, when comparing absolute 2-HG levels in both the circulating and urinary compartments, a significant difference in absolute urine 2-HG levels in patients with IDH-WT disease is noted between the two studies.The absolute plasma 2-HG values reported by Lombardi et al [28] (97.0 ng/mL for IDH-WT and 97.2 ng/mL for IDHmutant) were similar to values we detected in the serum, as were the creatinine-corrected median urinary 2-HG values in IDH1/2-mutant patients (4.6 mg/mL in Lombardi et al [28] vs. 2.926 mg/mL in our study).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Although it would appear intuitive that urine 2-HG levels would be comparatively elevated, as we have found, among a population of patients with IDH-mutant disease, the reason for the discordance with a previous report that observed lower urinary 2-HG levels in patients with IDH1-mutant compared with IDH-WT gliomas is unclear [28]. However, when comparing absolute 2-HG levels in both the circulating and urinary compartments, a significant difference in absolute urine 2-HG levels in patients with IDH-WT disease is noted between the two studies.The absolute plasma 2-HG values reported by Lombardi et al [28] (97.0 ng/mL for IDH-WT and 97.2 ng/mL for IDHmutant) were similar to values we detected in the serum, as were the creatinine-corrected median urinary 2-HG values in IDH1/2-mutant patients (4.6 mg/mL in Lombardi et al [28] vs. 2.926 mg/mL in our study).…”
Section: Discussioncontrasting
confidence: 99%
“…However, when comparing absolute 2-HG levels in both the circulating and urinary compartments, a significant difference in absolute urine 2-HG levels in patients with IDH-WT disease is noted between the two studies.The absolute plasma 2-HG values reported by Lombardi et al [28] (97.0 ng/mL for IDH-WT and 97.2 ng/mL for IDHmutant) were similar to values we detected in the serum, as were the creatinine-corrected median urinary 2-HG values in IDH1/2-mutant patients (4.6 mg/mL in Lombardi et al [28] vs. 2.926 mg/mL in our study). However, there is a large disparity in absolute urinary 2-HG values in patients with IDH-WT glioma, with the prior study reporting a median value of 7.3 mg/mL versus 1.694 mg/mL in our study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Conversely, serum 2HG levels correlate poorly with the IDH1/2 mutational status in glioma due to a limited BBB passage of D -2HG 56. Urine 2HG levels are higher in patients with IDH1 -mutated glioma than in patients with IDH1 wild-type glioma,57 although another study reported decreased 2HG levels in the urine of patients with IDH1 -mutated glioma and showed that the ratio of serum 2HG levels to urine 2HG levels is most predictive for the IDH1 mutational status in glioma 58. Most aforementioned measurements determined total 2HG levels and thus did not discriminate between the D -enantiomer of 2HG (which is specific for IDH1/2 mutations) and the L -enantiomer of 2HG (which is unspecific and is generated during hypoxia) 59 60.…”
Section: Introductionmentioning
confidence: 99%